2011
DOI: 10.3844/ajassp.2011.217.229
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Modeling of Microwave Assisted Epoxidation of Palm Acid Oil

Abstract: Problem statement: While microwave chemistry could well be the most convenient, rapid and energy-saving way to initiate a chemical reaction, the issues of thermal versus microwave specific effect remain unaddressed. Approach: A three-dimensional Finite Element Model (FEM) was developed to predict temperature profile during the enzymatic epoxidation of palm acid oil using microwave heating. Three-dimensional partial differential equations are formulated for the electromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This provides the molecule collision under microwave irradiation extra driving force, which results in higher rate of reaction under microwave irradiation as long as the enzyme is not deactivated by microwave. Under low power level of microwave irradiation, the active site of the enzyme molecules may undergo conformational changes and the microwave energy can modulate the configuration of enzyme molecules by accelerating the molecular rotation, which can provide more chance to make the substrates fit to the enzyme per unit of time [33,57,60]. Another aspect to note is that the amount of enzyme required to achieve maximum yield was also less for the case of microwave assisted hydrolysis.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…This provides the molecule collision under microwave irradiation extra driving force, which results in higher rate of reaction under microwave irradiation as long as the enzyme is not deactivated by microwave. Under low power level of microwave irradiation, the active site of the enzyme molecules may undergo conformational changes and the microwave energy can modulate the configuration of enzyme molecules by accelerating the molecular rotation, which can provide more chance to make the substrates fit to the enzyme per unit of time [33,57,60]. Another aspect to note is that the amount of enzyme required to achieve maximum yield was also less for the case of microwave assisted hydrolysis.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…Nonthermal effects or microwave effect has been observed in a number of microwave assisted catalytic or enzymatic reactions [33,57]. It has been proposed that at low power level of microwave irradiation, the significant contributor is the non-thermal effects, while the thermal effect plays only a minor role.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…This will enhance the efficiency of the enzyme. Non-thermal effects or microwave effect has been observed in a number of microwave assisted catalytic or enzymatic reactions (La Hoz et al, 2007;Yadav and Lathi, 2007;Saifuddin et al, 2011). Previous study on ethanol production from fresh cassava mash also showed that high viscosity caused resistance to solid-liquid separation and lower fermentation efficiency (Srikanta et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…This provides the molecule collision under microwave irradiation extra driving force compared to that under conventional heating, which results in higher rate of reaction under mmicrowave irradiation as long as the enzyme is not deactivated by microwave. The other contribution of the non-thermal effects is that microwave energy can also modulate the configuration of enzyme molecules by accelerating the molecular rotation and electron spin oscillation of the active site of the enzyme, which can provide more chance to make the substrates fit to the enzyme in unit of time (Saifuddin et al, 2011). The specific nature of this enzyme increases yield tremendously.…”
Section: Resultsmentioning
confidence: 99%
“…Non-thermal effects or microwave effect has been observed in a number of microwave assisted catalytic or enzymatic reactions 44 . It has been proposed that at low power level of microwave irradiation, the significant contributor is the non-thermal effects, while the thermal effect plays only a minor role.…”
Section: Microwave Assisted Hydrolysis Of Pomementioning
confidence: 99%